A prospective clinical study to evaluate the correlation of duration of kangaroo mother care and weight gain in low birth weight babies - Gagandeep, Vijayalaxmi; R., Chaithra; K., Febina (International Journal of Contemporary Pediatrics, 2019)
Background: Kangaroo Mother Care (KMC) is an alternative to conventional neonatal care for low birth weight (LBW) babies in low resource settings, this study is to evaluate the correlation between the duration of KMC given and average weight gain per day in low birth weight babies Method: It is an observational study, 106 low birth weight babies who were less than 1.8 kg, hemodynamically stable, accepting either direct breast feed or gavage feed were included in the study, duration of KMC given per day and weight was recorded daily until discharge. Babies were monitored for complications, if any babies were withdrawn from the study , necessary intervention was done. Average weight gain per day in these babies was estimated and correlated with the average duration of KMC. Results: Out of 120 eligible children 106 were selected for study of which 57 were male and 49 were female, 42 were less than 1.2 kg, 37 were between 1.21 kg to 1.5 kg and 27 were between 1.51 kg to 1.8 kg, there was statistically significant moderate correlation with Pearson r=0.6281 with p value <0.00001 and mean average weight gain was 5.27 in less than 6 hr to 8 hr, 9.08 in 8 hr to 10 hr, 11.87 in greater than 10 hrs of KMC Conclusion: The weight gain was found to increase with duration of KMC practice. hence authors recommend to increase the duration of KMC per day for the good average weight gain per day.